The effects of dividend policy, firm size, and green accounting on company value - Salsabila, Zahra; Novita Fitrah Ramadani; Wega Azizah (International Forum of Researchers and Lecturers, 2025)
The Indonesian manufacturing industry is currently facing intense pressure due to global economic fluctuations and domestic volatility, prompting a strategic reassessment of sustainability practices to maintain competitiveness. While firm value reflects investor confidence, discrepancies remain between operational performance and market valuation, particularly in highly profitable firms. This study aims to systematically investigate how internal corporate factors namely dividend policy, firm size, and green accounting influence firm value. Using a Systematic Literature Review (SLR) method, ten journal articles published between 2023 and 2025 were selected based on indexation (SINTA, Scopus, Copernicus), methodological clarity, and variable alignment. The articles were screened and analyzed using content analysis techniques, supported by Microsoft Excel and Mendeley for structured data extraction. The findings reveal that a stable dividend policy serves as a strong signal of financial stability, firm size reinforces strategic positioning and resource capacity, and green accounting strengthens legitimacy through sustainability disclosure. These factors jointly shape market perceptions and ultimately influence firm valuation. The synthesis supports both signal theory and legitimacy theory in explaining the transmission of value through internal policies. This study contributes theoretically by integrating financial and sustainability variables into a unified value framework and offers practical insights for corporate decision-makers seeking to align internal strategies with investor expectations. Limitations include reliance on secondary data and scope restricted to the manufacturing sector. Future studies should explore empirical validation through cross-sectoral analysis and primary data to enrich the findings.